DESCRIPTION OF SEXUAL BEHAVIOR RISK ON EARLY ADOLESCENT IN HOPE ISLAND VILLAGES OF THOUSAND ISLAND - Nadirahilah Susanto (HUMAN CARE JOURNAL, 2019)
Adolescent is a period of psychosexual development which at this stage are very prominent change is when the sexual function of maturity shown through behavior change. Indonesia Adolescent Reproductive Health Survey proves that nationally there is an increasing incidence of sexual intercourse than 3 million teens who claimed ever done premarital sexual behavior in 2007 to 3.7 milliion youth in 2012. This study is adescriptif study with 135 respondents as study sample are early adolescent in the Hope Island Villages 0f Thosand Island. The result of this study showed that most respondents are adolescent aged 11 years (40%), 52,6% were male and 47.4% female, 54.8% had sexual behavior risk and 21.5% of respondents ever do sexual intercourse. Advice to government, social agencies, and research institutions and community servicein college in order to perform adolescent reproductive health education to adolescent in Hope Island Villages of Thousand Island.